2002
DOI: 10.1093/jn/132.3.552s
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Chemoprevention: Timing and Mechanisms of Action in Murine Mammary and Prostate

Abstract: We investigated the potential of genistein, the primary isoflavone of soy, to protect against breast and prostate cancers in animal models. For mammary cancer studies, Sprague-Dawley rats were fed AIN-76A diet plus minus 250 mg genistein/kg diet. Dimethylbenz[a]anthracene was administered by gavage at d 50 postpartum to induce mammary tumors. Mammary cancer chemoprevention was demonstrated after prepubertal and combined prepubertal and adult genistein treatments but not after prenatal- or adult-only treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(177 citation statements)
references
References 41 publications
7
165
0
5
Order By: Relevance
“…tamoxifen, raloxifene) have been shown to decrease circulating IGF-I levels in previous human studies [27][28][29], and may also increase some IGFBP levels [27,28]. Additionally, studies in mouse models showed a reduction of serum IGF-I or IGF-I mRNA expression in breast or prostate tissue by phytoestrogens [52][53][54]. Residual + total energy intake in linear regression model.…”
Section: Discussionmentioning
confidence: 99%
“…tamoxifen, raloxifene) have been shown to decrease circulating IGF-I levels in previous human studies [27][28][29], and may also increase some IGFBP levels [27,28]. Additionally, studies in mouse models showed a reduction of serum IGF-I or IGF-I mRNA expression in breast or prostate tissue by phytoestrogens [52][53][54]. Residual + total energy intake in linear regression model.…”
Section: Discussionmentioning
confidence: 99%
“…The third IF of SPI is glycitin and its aglycone glycitein, but they are present only at low levels. As shown in Table 1, the findings obtained in rats exposed to SPI or purified genistein during the fetal-perinatal period vary from study to study, with three studies reporting an increase in the incidence of either carcinogen-induced tumours (Hilakivi-Clarke et al, 1999;Hilakivi-Clarke et al, 2002) or spontaneous hyperplasias and ductal carcinomas in situ (Foster et al, 2004), one study reporting a reduction in tumour multiplicity and % high grade tumours (Su et al, 2007a), and two studies reporting no effects (Lamartiniere et al, 2002;Pei et al, 2003). Two of these studies investigated the effects on mammary gland morphology in adult rats (Hilakivi-Clarke et al, 2002;Foster et al, 2004).…”
Section: Ratsmentioning
confidence: 99%
“…Since genistein is proposed as a chemoprevention agent for several tumour types (Mentor-Marcel et al, 2001;Lamartiniere et al, 2002), including breast and prostate cancers, we tested its ability to induce BRCA expression. Genistein caused dose-and time-dependent increases in BRCA1 and BRCA2 protein levels in two oestrogen-responsive breast cancer cell lines (MCF-7 and T47D) ( Figure 3D).…”
Section: Genistein Upregulates Brca1 and Brca2 Expressionmentioning
confidence: 99%